2023
DOI: 10.1371/journal.pone.0279907
|View full text |Cite
|
Sign up to set email alerts
|

Tin filter compared to low kV protocols - optimizing sinonasal imaging in computed tomography

Abstract: Objectives Paranasal sinus imaging due to chronic inflammatory disease is one of the most common examinations in head and neck radiology with CT imaging considered the current gold standard. In this phantom study we analyzed different low dose CT protocols in terms of image quality, radiation exposure and subjective evaluation in order to establish an optimized scanning protocol. Methods In a phantom study, an Alderson phantom was scanned using 12 protocols between 70–120 kV and 25–200 mAs with and without t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(74 reference statements)
0
2
1
Order By: Relevance
“…The dose reduction in the present study appears to be larger than previously reported 42,43 . In a diagnostic study, Mozaffary et al.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The dose reduction in the present study appears to be larger than previously reported 42,43 . In a diagnostic study, Mozaffary et al.…”
Section: Discussioncontrasting
confidence: 63%
“…The dose reduction in the present study appears to be larger than previously reported. 42,43 In a diagnostic study, Mozaffary et al evaluated the performance of a Sn filter-based CT (Sn150kV) compared with a routine low-dose CT (100 kV) and the standard protocol (120 kV) for the detection of urolithiasis, reporting a reduction of 28% and 66% in CTDIvol, respectively. 44 However, they elevated the applied kVp in the presence of the Sn filter compared with their routine protocol, whereas in the current study a reduced kVp compared with the routine protocol was employed.…”
Section: Discussionmentioning
confidence: 99%
“…This tin filter has a selection variation according to the energy level used between Sn100, Sn110, Sn120, and Sn140; Sn indicates the use of tin filters. For example, Sn100, at 100 kV energy, uses tin filters as energy filters (Schüle et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%